Proposed instructional materials based on an analysis of theme errors of first year students in the University of the Philippines Preparatory School - Goseco, Petronila (Sibal) 1927- (s.n.], 1964)
This study investigates the errors in the 1,140 compositions of first year students in UP Preparatory School in the school years 1961-1962 and 1962-1963. Instructional materials developed were based on these errors.